Fred - Simmonds, Posy. (New York : Puffin books, 1987)
The Night Sophie and Nick bury their dearly beloved cat Fred all Fred's cat friends arrive to reveal his nighttime self and give him a paper funeral and farewell.
Keywords: Cats -- Fiction; Death -- Fiction